2019
DOI: 10.5858/arpa.2019-0128-oa
|View full text |Cite
|
Sign up to set email alerts
|

Pathology Assessment of Femoral Head Resection Specimens: An Important Quality Assurance Procedure

Abstract: Context.— Decisions to perform hip arthroplasty rely on both radiographic and clinical findings. Radiologists estimate degree of osteoarthritis (OA) and document other findings. Arthroplasty specimens are sometimes evaluated by pathology. Objective.— To determine the frequency of pathologic changes not recognized clinically. Design.— Nine hundred fifty-three consecutive femoral head resections performed between January 2015 and June 2018, with recent radiologic and histologic study, were reviewed. We compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 16 publications
(42 reference statements)
1
16
0
Order By: Relevance
“…[ 10 ] 1999 Single center, retrospective US THA for any indication 562 0% $102.59 per specimen Against Layfield et al. [ 11 ] 2020 Single center, retrospective US THA for OA 953 0.52% None For Lin et al. [ 4 ] 2012 Single center, retrospective US Elective THA 457 0.22% $102.37 per specimen; no gain in QALY Against Liow et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 10 ] 1999 Single center, retrospective US THA for any indication 562 0% $102.59 per specimen Against Layfield et al. [ 11 ] 2020 Single center, retrospective US THA for OA 953 0.52% None For Lin et al. [ 4 ] 2012 Single center, retrospective US Elective THA 457 0.22% $102.37 per specimen; no gain in QALY Against Liow et al.…”
Section: Resultsmentioning
confidence: 99%
“…Of the articles that commented on the need for routine pathologic examination of femoral heads retrieved during THA, 58% (7 of 12 articles) advised against this practice as it was not found to change patient management [ 4 , 5 , 8 , 10 , 12 , 13 , 15 ]. It is our opinion that the remaining 5 articles that favored routine pathologic examination did so after mischaracterizing many pathologic diagnoses that did not impact patients’ clinical course as discordant [ 6 , 7 , 9 , 11 , 17 ]. This resulted in an overvaluation of routine femoral head pathology, which skewed analyses of cost-effectiveness and ultimately these articles’ conclusions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among their sample, most discrepancy came in the form of unsuspected diagnosis of osteonecrosis of the femoral head, with a much smaller percentage secondary to osteomyelitis. 3 Conversely, studies from orthopaedic surgeons have called into question both the existence of a discrepancy and the clinical significance of these diagnostic discrepancies when present. In a review of 715 consecutive cases of total joint arthroplasty including 283 THAs and 432 TKAs by Campbell et al, in only 3 of the 283 THAs was the pathology report discordant with the preoperative clinical diagnosis.…”
Section: Utility Of Histopathologic Features Of Femoral Heads Obtaine...mentioning
confidence: 99%
“…The study by Besser 6) , which reported unsuspected tuberculosis detected during a total knee replacement, is often cited as justification for the practice, and additional studies such as a review of 1,794 femoral heads by DiCarlo et al 7) reported discrepancies between operative and pathological diagnosis in 5.4% of cases, as well as the discovery of seven morbid conditions not noted clinically. A recent study by Layfield et al 8) , which noted a significant percentage of patients undergoing hip arthroplasty where significant pathological changes were not recognized preoperatively by the orthopaedic surgeon, advocated for the continued use of pathology for diagnosis.…”
Section: Introductionmentioning
confidence: 99%